Effect of Dietary Supplementation of Chitosan on Blood Biochemical Profile of Laying Hens - Hernawan, Elvia; Adriani, Lovita; Mushawwir, Andi; Cahyani, Chandrawati; Darmawan (Pakistan Journal of Nutrition, 2017)
Background and Objective: Chitosan is a natural alkaline polysaccharide and widespread in nature. A study was conducted to evaluate the effect of dietary supplementation of chitosan on blood biochemical parameters like cholesterol, malondialdehyde (MDA), creatinine and total leucocytes. Methodology: One hundred laying phase hens, aged 28 weeks were used in the study. The birds were divided into 2 treatment groups each having 3 replicates of 10 birds each. Group I served as control and was fed basal diet. In Group II, basal diet was supplemented with chitosan at 150 ppm g–1 by spraying method. Results: The results showed that the chitosan inclusion in the diet of layer pullets significantly (p